UJI IN VITRO DAN IN SILICO SENYAWA 5,7,2’,5’-TETRAHYDROXY FLAVAN-3-OL TERHADAP ENZIM ALPHA GLUCOSIDASE - Frengki Frengki; Deddi Prima; Fatma Sri Wahyuni; Daan Khambri; Henny Vanda; Noni Zakiah; Jamilah Abbas; Berna Elya (Jurnal Fitofarmaka Indonesia, 2018)
Several of Calophyllums genus have been searched and proven as medicinal plants and Calophyllum macrophyllum is one of its genus. We have been isolated a compound from ethyl acetate fraction of the stem-bark. The compound was flavan-3-ol (5,7,2’,5’-tetrahydroxy flavan-3-ol). This research aimed to determine inhibition antidiabetic activity and affinity of its compound on α-glycosidase enzyme. In vitro antidiabetic effect shown by IC50 9.10 µg/ml and docking by Arguslab 4.01 shown by ΔG -10,24 kkal/mol as in silico test. The inhibition activity of flavan-3-ol against the α-glucosidase enzyme that is very strong shows its promising potential as a candidate for antidiabetic drugs.